Monitoring Serangan Dan Pengendalian Hama Ulat Api (Setothosea Asigna) Pada Tanaman Kelapa Sawit Di Perkebunan Tanah Gambus Pt. Socfin Indonesia - Hutauruk, Sixtus (AGROSUSTAIN, 2025)
Monitoring of Attacks and Control of Fire Caterpillar Pests (Setothosea asigna) on Oil Palm Plants at the Tanah Gambus Plantation of PT. "Socfin Indonesia" aims to describe the results of monitoring and control methods for fireworms in oil palm plantations. This research was conducted in the Three Divisions of Tanah Gambus Plantation, Batu Bara Regency, North Sumatra, from January to April 2024. The study used descriptive methods through field observations, sampling at census points, and re-censuses. Monitoring was conducted to monitor fireworm populations, while primary control was carried out through fogging with Santador 25 EC insecticide and diesel. This paper presents an integrated approach to controlling fireworms, which damage oil palm productivity. This study highlights the important role of routine monitoring, which involves mapping infestation points in specific blocks and establishing infestation criteria (light, moderate, and heavy) to determine appropriate control methods. In addition to chemical techniques, control also considered alternative control methods such as biological control with natural predators. The results showed variations in fireworm populations across blocks, influenced by environmental conditions such as high humidity. Post-control re-censtrals were conducted to measure the effectiveness of these methods